Acute Liver Failure in a Healthy Young Female With COVID-19. Issue 3 (22nd August 2021) - Orandi, Babak John; Li, Geling; Dhall, Deepti; Bajpai, Prachi; Manne, Upender; Arora, Nitin; Lu, Ailing; Coronado, Ana Carolina; Kassel, Rachel; Pinninti, Swetha; Lewis, Cora Elizabeth; Chapleau, Christopher; et al.
Abstract : Several well-described manifestations of infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) have been reported. Among them, a transient elevation of liver enzymes is the typical presentation of coronavirus disease 2019 (COVID-19) liver-related injury. The mechanism of liver involvement is likely a combination of viral injury and immune-mediated inflammation. In contrast, acute liver failure in the setting of COVID-19 has rarely been reported. Herein, we report a case of pediatric acute liver failure in a previously healthy female adolescent infected with SARS-CoV-2 with biopsy evidence of replicating virus in hepatocytes, which has not been previously reported.